Upacara Mājar-ajar di Pura Agung Besakih: Konsep dan Implementasinya - Artayasa, I Putu; Suda, I Ketut; Wirawan, I Gusti Bagus (Jurnal Penelitian Agama Hindu, 2024)
Balinese people have a lot of traditional knowledge, called rural community knowledge. However, the influence of modern science and technology has resulted in many Balinese local wisdom values being transformed and marginalized because they do not follow the principles of modernism. One of them is the mājar-ajar ceremony carried out by Hindus at Besakih Temple. As a result, there was a shift in the ceremony process. Based on the ancient Dresta text, 21 temples must be visited when carrying out the mājar-ajar ceremony at Besakih Temple. However, in reality, only a few people currently visit it; even those do it centrally at the Dalem Puri Temple. This research aims to explore the mājar-ajar procession, both textually and contextually. This research uses qualitative methods with a religious anthropology approach and an interpretive paradigm. The data obtained was analyzed using qualitative-interpretative analysis techniques. The results obtained include first, the factors that cause differences between the concept and implementation of the mājar-ajar procession at Besakih Temple, namely 1) differences in the meaning of the mājar-ajar ceremony, 2) meaning based on literary texts, meaning based on social context, 3) meaning based on ideology and 4) because of the actor's role. Second, the mājar-ajar procession at Besakih Temple can be divided into several parts, namely the mājar-ajar procession as a symbol system, as a sign system, and as a social agreement. Third, such differences affect the Balinese people's social, cultural, economic, and religious life. An interesting finding from this research is the attitude of pragmatism that has hit people's lives, resulting in social credit (ngoopin, matulungan, and cooperation) in the lives of Hindu communities in Bali becoming thin.